Myles Brand: A Leader Deeply Committed to Diversity, Inclusiveness, and Social Justice - Wiggins, David K. (Journal of Intercollegiate Sport, 2021)
Myles Brand: A Leader Deeply Committed to Diversity, Inclusiveness, and Social JusticeMyles Brand will probably always best be remembered as the Indiana University president who fired legendary basketball coach Bobby Knight. It is unfortunate since Brand, as a scholar, president of two major universities, and Executive Director of the NCAA, accomplished a great many things on behalf of students and as an enthusiastic proponent of the educational value of intercollegiate athletics and sport more generally. At all times and in everything he did, Brand exhibited as a leader a deep commitment to diversity, inclusiveness, and social justice. It was especially noticeable and on full display during his time as Executive Director of the NCAA, a position he held from 2002 until his untimely death from cancer in 2009. As this essay illustrates, Brand’s commitment to diversity, inclusiveness, and social justice was made clear through the academic reform movement he helped initiate and in fights to eliminate Native American mascots and other disparaging images, secure more head coaching positions for Blacks, and maintain original Title IX guidelines that had allowed women increasing opportunities to participate in highly competitive athletics. Although not always successful in these efforts, especially in seeing more Blacks hired as head coaches, Brand was largely effective in leading the effort to implement academic reform measures, rid sport of insulting Native American imagery, and guard against those who were